The Effect of Intrinsic, Extrinsic Motivation and Organizational Culture on Employee Job Performance at the Yogkarta Regional Disaster Management Agency Office (Office Case Study in Yogyakarta City) - Tangkur, Eventinus Darman; Subiyanto, Didik; kirana, Kusuma Chandra (Jurnal Ekonomi Balance, 2023)
Employee engagement is one of the key success factors that is always needed or strived for in almost every company. The work of employees in the company is very important. Achieving company goals requires high performance in all efforts to cooperate with employees. Employee performance can be achieved through 3 factors, namely (i) Intrinsic motivation is the motivation that makes someone perform well that comes from himself, (ii) Extrinsic motivation is the motivation of employees to complete their work. culture is an individual organization or company that can complete the work of employees, (iv) The purpose of this research is to identify and the importance of differences between intrinsic motivation, extrinsic motivation, and organizational culture on employee performance at the Yogyakarta Regional Disaster Management Agency office. The following research uses a quantitative approach. The population in this research is 45 employees. The sampling method was carried out using a non-probability method and the sampling technique was purposive sampling. Data analysis using IBM SPSS application. The results of the research variable Intrinsic Motivation (X1) have no significant effect on Employee Performance (Y) as indicated by the results of the t test and the calculated t value of 0.767 < the t table value of 2.021 and its significance. 0.449 which means more than 0.05. Then the Extrinsic Motivation variable (X2) has no significant effect on employee performance (Y) which is shown from the results of the t test, the t count value is 0.094 <t table value 2.021, which is 0.926, which means more. Do 0.05 Differences in organizational culture (X3) have a positive effect on employee performance (Y). This is evidenced by the results of the t test, with a significance value of t count 6.110 > t table value of 2.021. 0.001 which means 0.05 is smaller than 05